Legal Protection Against Employment Laws Related to the Granting of Leave in Accordance with Applicable Regulations - Karen Eklesia Gabriella Kaendo (CV. Rayyan Dwi Bharata, 2023)
The purpose of this writing is to find out how the legal protection of employment law relates to the granting of leave in accordance with applicable regulations. This type of written research method is qualitative in nature with the type of document. Qualitative research is a type of research whose results are not based on statistics or other calculations. Work is one of the efforts of humans as social beings to fulfill their basic needs. Legal protection for workers is needed considering that the government often ignores equality and fairness in the workplace. Legal protection for maternity leave for pregnant employees from several companies which is regulated in the employment contract, ie. the right to maternity leave and payment for maternity leave. In addition, based on the research results it is also known that in several companies the company's responsibility for maternity leave rights includes granting maternity rights. With the right to maternity leave, pregnant workers do not have to work shifts and pay during maternity leave. From an Islamic point of view, the aqad or contract that a company makes with its employees fulfills the principle of the contract. Because according to the clause that has been agreed before. However, there are still several rights that have not been fulfilled under Article 83 of the Labor Law No. 13 of 2003, namely granting the right to breastfeed a child if it has to be done during working hours.